it - Information Technology : Methods and Applications of Informatics and Information Technology (De Gruyter Oldenbourg, 1959)
it - Information Technology is a strictly peer-reviewed scientific journal. It is the oldest German journal in the field of information technology. Today, the major aim of it - Information Technology is highlighting issues on ongoing newsworthy areas in information technology and informatics and their application. It aims at presenting the topics with a holistic view.